2002
DOI: 10.1007/bf03000106
|View full text |Cite
|
Sign up to set email alerts
|

Changes in regional cerebral blood flow in irradiated regions and normal brain after stereotactic radiosurgery

Abstract: These results suggest that subclinical regional CBF reduction occurs after SRS in the normal brain in out-of-field of radiation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
18
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 10 publications
3
18
0
Order By: Relevance
“…Decreased glucose metabolism in the radiation-injured or peri-radiation-injured brain tissue [46] and in brain regions receiving over 40 Gy radiation [47] has also been reported. Similar decreases in cerebral blood flow were observed in the targeted and surrounding healthy tissue weeks following stereotaxic radiosurgery [48]. These studies illustrate that radiation therapy induces a long-term reduction in vascular density that is followed by decreased cerebral blood flow and metabolism.…”
Section: Vasculature Effects Of Wbrtsupporting
confidence: 59%
“…Decreased glucose metabolism in the radiation-injured or peri-radiation-injured brain tissue [46] and in brain regions receiving over 40 Gy radiation [47] has also been reported. Similar decreases in cerebral blood flow were observed in the targeted and surrounding healthy tissue weeks following stereotaxic radiosurgery [48]. These studies illustrate that radiation therapy induces a long-term reduction in vascular density that is followed by decreased cerebral blood flow and metabolism.…”
Section: Vasculature Effects Of Wbrtsupporting
confidence: 59%
“…Previous studies by us and others have shown that WBI also results in a significant microvascular rarefaction (Ljubimova et al 1991;Warrington et al 2012), particularly in the hippocampus, the region responsible for spatial learning and memory (Warrington et al 2011). It is likely that neurovascular uncoupling and microvascular rarefaction act synergistically to impair regional blood supply in the brain (Fuss et al 2000;Taki et al 2002), exacerbating cognitive decline. It is important that both neurovascular dysfunction and microvascular rarefaction are manifested relatively early (within 3 months) after WBI and their onset coincides with the appearance of cognitive symptoms.…”
Section: Discussionmentioning
confidence: 94%
“…39 However, in a recent study on 13 patients, a reduction of regional CBF at 2 weeks and 3 months after stereotactic radiosurgery in out-of-field areas (Ͻ5 Gy) was observed by 99m Tc-HMPAO scintigraphy. 58 High precision stereotactic radiosurgery is used to deliver high doses of radiation to small intracranial tumors, while the dose to surrounding normal brain tissue is minimized due to the steep radiation dosage decline at the border of the target volume. 5,8 In our study, the normal brain parenchyma examined was only affected by radiation doses less than 0.5 Gy, 38 which might explain the conflicting results.…”
Section: Investigative Radiology • Volume 39 Number 5 May 2004mentioning
confidence: 99%